Optimal design and operation of distributed low-carbon energy technologies in commercial buildings. (1st January 2018) - Acha, Salvador; Mariaud, Arthur; Shah, Nilay; Markides, Christos N.
Abstract: Commercial buildings are large energy consumers and opportunities exist to improve the way they produce and consume electricity, heating and cooling. If energy system integration is feasible, this can lead to significant reductions in energy consumption and emissions. In this context, this work expands on an existing integrated Technology Selection and Operation (TSO) optimisation model for distributed energy systems (DES). The model considers combined heat and power (CHP) and organic Rankine cycle (ORC) engines, absorption chillers, photovoltaic panels and batteries with the aim of guiding decision makers in making attractive investments that are technically feasible and environmentally sound. A retrofit case study of a UK food distribution centre is presented to showcase the benefits and trade-offs that integrated energy systems present by contrasting outcomes when different technologies are considered. Results show that the preferred investment options select a CHP coupled either to an ORC unit or to an absorption chiller. These solutions provide appealing internal rates of return of 28–30% with paybacks within 3.5–3.7 years, while also decarbonising the building by 95–96% (if green gas is used to power the site). Overall, the TSO model provides valuable insights allowing stakeholders to make well-informed decisions when evaluating complex integrated energy systems. Highlights: Optimal integrated selection and operation of distributed energy systems (DES). Model informs stakeholders/decision-makers of technoeconomic investment trade-offs. DES provide major security of supply and resource efficiency benefits. CHP-based solutions offer better returns (28–30%) than PV-battery combination (13%). CHP-ORC and CHP-absorption chiller solutions have paybacks within 3.5–3.7 years.